2019
DOI: 10.1016/j.schres.2018.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting and affective priming in individuals with negative schizotypy

Abstract: Previous studies have demonstrated that patients with schizophrenia and individuals with schizotypy experience decreased anticipatory pleasure. However, it is unclear whether this decrease is contributed by altered reward processing at the proximal or distal future. In order to investigate the preference for receiving rewards in the proximal or distal future for individuals with schizophrenia spectrum disorders, individuals with either high or low levels of negative schizotypy performed a delay discounting tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 79 publications
(104 reference statements)
2
8
0
3
Order By: Relevance
“…The steeper discounting rate has been associated with greater severity of cognitive impairment (Ahn et al, 2011; Brown et al, 2018; Heerey et al, 2007; Yu et al, 2017) and negative symptoms (Horan et al, 2017) in some studies; however, other studies have found null or inconsistent results (Heerey et al, 2007; Horan et al, 2017; Weller et al, 2014). Similar findings have emerged in first-degree relatives (Ho, Barry, & Koeppel, 2018) and individuals with high negative schizotypy traits (Cai et al, 2018) [however, see Wang et al (2018) and Yu et al (2017)]. Collectively, these findings suggest that impairments in value representation exist both in individuals with SZ, as well as first-degree relatives and those with schizotypal traits who are putatively at risk for psychosis.…”
Section: Introductionsupporting
confidence: 59%
“…The steeper discounting rate has been associated with greater severity of cognitive impairment (Ahn et al, 2011; Brown et al, 2018; Heerey et al, 2007; Yu et al, 2017) and negative symptoms (Horan et al, 2017) in some studies; however, other studies have found null or inconsistent results (Heerey et al, 2007; Horan et al, 2017; Weller et al, 2014). Similar findings have emerged in first-degree relatives (Ho, Barry, & Koeppel, 2018) and individuals with high negative schizotypy traits (Cai et al, 2018) [however, see Wang et al (2018) and Yu et al (2017)]. Collectively, these findings suggest that impairments in value representation exist both in individuals with SZ, as well as first-degree relatives and those with schizotypal traits who are putatively at risk for psychosis.…”
Section: Introductionsupporting
confidence: 59%
“…Without individuals without schizotypy, we could not directly compare their performance in delay discounting task. However, several studies have shown that individuals with schizotypy demonstrated more impulsive choice (Cai et al, 2019;Li et al, 2016). Moreover, the main aim of this study was to explore whether EFT was related to lower delay discounting in individuals with schizotypy compared to ERT and our findings confirmed this.…”
Section: Discussionsupporting
confidence: 81%
“…Schizophrenia has been considered as a continuum (Ettinger, Meyhöfer, Steffens, Wagner, & Koutsouleris, 2014); schizotypy is within the continuum (Siever, Kalus, & Keefe, 1993) and demonstrate similar but milder neurobiological (Siever et al, 1995(Siever et al, , 2002 and cognitive (Barch et al, 2004;Ettinger et al, 2014;Siever et al, 2002) deficits as in schizophrenia. Previous studies revealed that individuals with negative schizotypy had higher discounting rate than healthy controls (Cai et al, 2019;Li et al, 2016), indicating that individuals at risk for schizophrenia had greater preference for immediate rewards. Given that poor performance in delay discounting task may cause bad consequences (e.g., a high discounting rate can be a high risk factor for drug addiction; Bickel, Koffarnus, Moody, & Wilson, 2014), it is important to reduce discounting rate and improve the ability to resist immediate rewards in these individuals with some strategies.…”
Section: Introductionmentioning
confidence: 97%
“…, 2015 ) or long (15 seconds, Augustine and Larsen, 2011 ) exposure to negative emotional pictures increases the propensity to choose smaller-sooner over larger-later rewards, whereas exposure to positive pictures shifts decisions toward choosing larger-later rewards ( Guan et al. , 2015 ; Cai et al. , 2019 ).…”
Section: Introductionmentioning
confidence: 99%